Waqf in Penang from the Historical Perspective - Ahmad Rodzi Pawanteh; Rubai Ahmad Munawar; Hendrianto MA; Sudin Haron (Lembaga Bale Literasi, 2025)
The Waqf is a crucial instrument in Islamic economics that is gaining increasing attention in contemporary academic studies. Researchers' attention is no longer limited to the Islamic banking and finance sector, but has shifted to the sustainable management of Islamic wealth through waqf instruments. Malaysia, as a pioneer in the development of global Islamic finance, plays a significant role in modernizing waqf management. The country consists of 14 states, each with the authority to manage waqf assets within its territory. Among these states, Penang Island is known as a successful example of effective and innovative waqf management. This study aims to examine the development of waqf in Penang from its early days to modern practice using a descriptive normative approach and a